The EIF2AK4/rs4594236 AG/GG Genotype Is a Hazard Factor of Immunoglobulin Therapy Resistance in Southern Chinese Kawasaki Disease Patients - Yu, Hongyan; Liu, Fucheng; Chen, Kaining; Xu, Yufen; Wang, Yishuai; Fu, Lanyan; Zhou, Huazhong; Pi, Lei; Che, Di; Li, Hehong; Gu, Xiaoqiong (Frontiers in Genetics, 2022)
Background Kawasaki disease (KD) is an acute, self-limited vasculitis disorder of unknown etiology in children. Immunologic abnormalities were detected during the acute phase of KD, which reflected the effect cells of activated immune system increased cytokines production markedly. High-dose intravenous immunoglobulin (IVIG) therapy is effective in resolving inflammation from KD and reducing occurrence of coronary artery abnormalities. However, 10-20% of KD patients have no response to IVIG therapy, which were defined as IVIG resistance. Furthermore, these patients have persistant inflammation and increased risk of developing coronary artery aneurysms (CAA). EIF2AK4 is a stress sensor gene and can be activated by pathogen infection. In addition, the polymorphisms of EIF2AK4 were associated with various blood vessel disorders. However, it remains unclear whether the EIF2AK4 gene polymorphisms were related to IVIG therapy outcome in KD patients. Methods EIF2AK4/rs4594236 polymorphism was genotyped in 795 IVIG response KD patients and 234 IVIG resistant KD patients through TaqMan real-time polymerase chain reaction. The odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the strength of association between EIF2AK4/rs4594236 polymorphism and IVIG therapeutic effects. Results Our results showed that EIF2AK4/rs4594236 AG/GG genotype was significantly associated with increased risk to IVIG resistance compared to AA genotype (AG versus AA: adjusted ORs=1.71, 95% CIs = 1.17-2.51, p= 0.0061;GG versus AA: adjusted ORs =2.09, 95% CIs= 1.36-3.23, p= 0.0009; AG/GG versus AA: adjusted ORs=1.82, 95% CIs= 1.27-2.63, p= 0.0013; and GG versus AA/AG: adjusted ORs=1.45, 95% CI= 1.04-2.02, p= 0.0306). Furthermore, the stratified analysis of age and gender in KD cohort indicated that male patients carrying rs4594236 AG/GG genotype tends to be more resistant to IVIG therapy compared to female patients. Conclusion These results suggested that EIF2AK4/rs4594236 polymorphism might be associated with increased risk of IVIG resistance in southern Chinese KD patients.